Decentralized sliding mode control using an event-triggered mechanism for discrete interconnected Hammerstein systems - Znidi, Aicha; Nouri, Ahmed Said (Zielona Góra: Uniwersytet Zielonogórski)
An innovative control strategy addressing the complexities of discrete interconnected nonlinear Hammerstein subsystems is presented. The approach combines decentralized sliding mode control (DSMC) with an event-triggered mechanism (ETM) to efficiently manage complex systems characterized by discrete elements, nonlinear behavior, and interconnections.
Keywords: sliding mode control; event-triggered mechanism; discrete interconnected systems; Hammerstein models